EVALUASI KONDISI LINGKUNGAN PERAIRAN ESTUARIA TELUK KLABAT, BANGKA PADA MUSIM TIMUR - Suhendar I Sachoemar (Jurnal Teknologi Lingkungan, 2005)
The environmental situation of the estuarial ecosystem Teluk Klabat that islocated at the northwestern coastal area of Bangka was evaluated on the basis of the physical, chemical and biological data derived from direct in-situ field survey during the southeast monsoon (dry season). The objective of this study is to understand the environmental characteristics and water quality status of the Teluk Klabat to support fisheries development within this area. The result shows that the sedimentation process at theTeluk Klabat has been ocurred excessively and it caused decreasing of the bathymetry reached only 1 m that is found almost in a whole of the coast line area at the inner side of the Teluk Klabat and it extended up to more than 2.5 km from that coast line. More over, the terrestrial environment seem to have strong effect on the degradation of the water quality at the Teluk Klabat that is shown by high concentration of the nutrient (nitrate, phosphate, silicate) and heavy metal such as Pb and Cd. While chlorophyll-a concentration was also high. It indicates that the Teluk Klabat tend to be eutrophycation.